2007
DOI: 10.4018/irmj.2007070106
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Computer Self-Efficacy and System Complexity on Technology Acceptance

Abstract: Despite the prevalence of computing in all aspects of society, some computer systems may not be fully accepted by their intended users or become underutilized. Thus, acceptance and use of information technologies remain a paramount issue in information systems (IS) research and practice. Extending previous research by integrating computer self-efficacy and perceived system complexity as external variables to the technology acceptance model (TAM), this study examines the direct and indirect effects of these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 45 publications
(70 reference statements)
8
20
0
2
Order By: Relevance
“…These two studies have showed that system self-efficacy is a strong determinant of perceived ease of use before hands-on experience. Many previous empirical studies have also found system self-efficacy had a positive effect on perceived ease of use [8,50]. …”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…These two studies have showed that system self-efficacy is a strong determinant of perceived ease of use before hands-on experience. Many previous empirical studies have also found system self-efficacy had a positive effect on perceived ease of use [8,50]. …”
Section: Literature Reviewmentioning
confidence: 98%
“…Self-efficacy is a key element in SCT and refers to the judgments of people regarding their capabilities to organize and execute courses of action required to perform a task. Self-efficacy affects the behaviors that people choose to perform, the amount of effort they are prepared to exert, and the length of their persistence to overcome obstacles [8,15,47]. According SCT, self-efficacy is a major determinant of an individual’s task performance and has been found to have diverse psychological and behavioral effects in many areas of human psychosocial functioning [15,46].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Atitudes positivas perante o uso do computador, baixa ansiedade, confiança no uso da máquina, propensão para utilizar mais computadores e laboratórios de informática ou mais acessos ao software de apoio à aprendizagem também se confirmaram como aspectos correlacionados como nível de AEC dos indivíduos (Agarwal et al, 2000;Hasan, 2006;Ismail, Mahmud, Nor, Ahmad & Rahman, 2011;Khorrami-Arani, 2001;Mcilroy, Sadler & Boojawon, 2007;Noiwan, Piyawat, & Norcio, 2005;Tams, Craig & Murphy, 2011;Torkzadeh et al, 2006;Torkzadeh et al, 1999). Nas correlações negativas entre a autoeficácia e outras variáveis foi encontrado, no artigo de Agarwal et al (2000), que o nível de estresse associado ao uso da internet apresentou-se negativamente correlacionado com o nível de autoeficácia no uso da internet dos respondentes.…”
Section: Principais Resultados Das Pesquisas Sobre Aecunclassified
“…Como variável critério, os pesquisadores Barbeite e Weiss (2004) confirmaram a autoeficácia no uso de computadores como fator antecedente à percepção de conforto no uso de computadores. Com resultado parecido, Hasan (2006) investigou o modelo TAM (Technology Acceptance Model -Modelo de Aceitação de Tecnologia) proposto por Davis, Bagozzi e Warshaw (1989), e concluiu que a AEC pode ser considerada variável antecedente à percepção do aprendiz sobre a facilidade no uso de computadores, influenciando-a de maneira positiva.…”
Section: Principais Resultados Das Pesquisas Sobre Aecunclassified